PROBLEMATIKA PENGEMBANGAN PAUD DI WILAYAH PEDESAAN: STUDI KASUS DI DESA HABIRAU KANDANGAN - Asiah, Asiah; Risma, Nor; Azizah, Wafiq; Hasanah, Ghina (Institut Agama Islam Ngawi, 2024)
Early childhood education (PAUD) is education that is organized as a comprehensive coaching effort towards the growth and development of children from the ages of 0-6 years, by providing stimulus to aspects of the child's growth and development so that they can run optimally according to their stages. Early age is also known as the golden age in various aspects of children's growth and development. This period is also a period of great potential for children to learn various kinds of knowledge and skills as preparation for children to enter the next period. Therefore, society, parents and educators must work together in developing it so that aspects of children's growth and development can be stimulated properly. For this reason, researchers are interested in researching the problems of developing PAUD in rural areas. The research method used was qualitative research by taking samples in Habirau village and the Al-Husna early childhood education institution Jalan Guerilla, Daha Selatan District, Kandangan, South Kalimantan. The subjects in this research were 10 informants including 4 teaching staff and 6 parents or the community. The results of the research show that people in Habirau Kandangan village consider PAUD, especially play groups (KB), to be not very important for children. This is due to the lack of knowledge of parents, the community and educators regarding the importance of educating children of their own age, starting from birth until the age of 6 years.